TESS discovery of a sub-Neptune orbiting a mid-M dwarf TOI-2136. Issue 3 (30th May 2022) - Gan, Tianjun; Soubkiou, Abderahmane; Wang, Sharon X; Benkhaldoun, Zouhair; Mao, Shude; Artigau, Étienne; Fouqué, Pascal; Arnold, Luc; Giacalone, Steven; Theissen, Christopher A; Aganze, Christian; Burgasser, Adam; et al.
ABSTRACT: We present the discovery of TOI-2136 b, a sub-Neptune planet transiting a nearby M4.5V-type star every 7.85 d, identified through photometric measurements from the Transiting Exoplanet Survey Satellite ( TESS ) mission. The host star is located 33 pc away with a radius of R * = 0.34 ± 0.02 R⊙, a mass of 0.34± 0.02 M_, and an effective temperature of 3342 ± 100 K. We estimate its stellar rotation period to be 75 ± 5 d based on archival long-term photometry. We confirm and characterize the planet based on a series of ground-based multiwavelength photometry, high-angular-resolution imaging observations, and precise radial velocities from Canada–France–Hawaii Telescope (CFHT)/SpectroPolarimètre InfraROUge (SPIRou). Our joint analysis reveals that the planet has a radius of 2.20 ± 0.17 R⊕ and a mass of 6.4 ± 2.4 M⊕ . The mass and radius of TOI-2136 b are consistent with a broad range of compositions, from water-ice to gas-dominated worlds. TOI-2136 b falls close to the radius valley for M dwarfs predicted by thermally driven atmospheric mass-loss models, making it an interesting target for future studies of its interior structure and atmospheric properties.